The Effect of Written Expression on Severity of Gastrointestinal Symptoms in Patients With Irritable Bowel Syndrome - Marzieh Borjian Borujeni; Mehrnoosh Inanlou; Mohammad Heidari; Mehdi Nikkhah; Shima Haghani; Alice Khachian (Iran University of Medical Sciences, 2021)
Background & Aims: Irritable Bowel Syndrome (IBS) is one of the most common gastrointestinal disorders that significantly affects patients' quality of life. This study aimed to determine the effect of written expression on the severity of gastrointestinal symptoms in patients with IBS.  Materials & Methods: This clinical trial study was conducted in 2019 on 71 patients with IBS who were referred to the gastrointestinal clinics of Firoozgar and Rasoul Akram hospitals in Tehran, were selected using a continuous sampling method based on inclusion criteria and randomly (permuted block randomization) assigned to two control and intervention groups. A questionnaire on demographic characteristics and symptom severity index (SI-IBS) was completed by both groups. A white booklet with a particular format was given to each participant to express their emotions in writing in the intervention group. A weekly written expression of the patient's feelings for 15-30 min was done at home for one month. After one month, the SI-IBS questionnaire was completed again by both groups. Finally, the questionnaires were analyzed using SPSS v. 16 software. Results: After the intervention, the severity of gastrointestinal symptoms in the experimental group decreased significantly compared to before the intervention (P= 0.016). However, there was no statistically significant difference between the mean scores of gastrointestinal symptoms in the experimental and control groups one month after the intervention (P= 0.438). Conclusion: Execution of written expression in this study did not cause a statistically significant difference in the score of gastrointestinal symptoms in patients with irritable bowel syndrome but was associated with a decrease in the severity of gastrointestinal symptoms in patients in the experimental group. This non-pharmacological intervention can be considered a practical and easy method and pharmacological treatment for patients with this syndrome.